Enteral Nutrition in Pediatric Patients Undergoing Hematopoietic SCT Promotes the Recovery of Gut Microbiome Homeostasis - D’Amico, Federica (Nutrients, 2019)
Hematopoietic stem cell transplantation (HSCT) is the first-line immunotherapy to treat several hematologic disorders, although it can be associated with many complications reducing the survival rate, such as acute graft-versus-host disease (aGvHD) and infections. Given the fundamental role of the gut microbiome (GM) for host health, it is not surprising that a suboptimal path of GM recovery following HSCT may compromise immune homeostasis and/or increase the risk of opportunistic infections, with an ultimate impact in terms of aGvHD onset. Traditionally, the first nutritional approach in post-HSCT patients is parenteral nutrition (PN), which is associated with several clinical adverse effects, supporting enteral nutrition (EN) as a preferential alternative. The aim of the study was to evaluate the impact of EN vs. PN on the trajectory of compositional and functional GM recovery in pediatric patients undergoing HSCT. The GM structure and short-chain fatty acid (SCFA) production profiles were analyzed longitudinally in twenty pediatric patients receiving HSCT—of which, ten were fed post-transplant with EN and ten with total PN. According to our findings, we observed the prompt recovery of a structural and functional eubiotic GM layout post-HSCT only in EN subjects, thus possibly reducing the risk of systemic infections and GvHD onset.